Penggunaan Media Kartu Kata untuk Meningkatkan Kemahiran Membaca Siswa Kelas XI - Setiawan, Muhammad Arif; Maziyah, Laily (Journal of Language Literature and Arts, 2024)
This research aimed to explore the effectiveness of using word card media in enhancing the reading proficiency of grade XI students, specifically focusing on Arabic language reading skills. The study employed a classroom action research (CAR) design with a qualitative descriptive approach, conducted over two cycles, each comprising two sessions: planning, action, observation, and reflection. The participants were 14 students from class XI at SMAS Darul Quran Singosari Malang. Data collection methods included oral and written reading tests, interviews, observation, and documentation. Data analysis followed a descriptive approach involving data collection, reduction, presentation, and drawing conclusions. The results revealed a positive impact of word card media on students' Arabic reading proficiency across both cycles. In the pre-cycle assessment, students scored an average of 43.9. Following the implementation of word card media in cycle I, the average score increased to 68.9, with a classical completeness percentage of 64. In cycle II, students' reading proficiency further improved, with an average score of 82.8 and a completion rate of 92.8 percent. These findings suggest that the utilization of word card media effectively enhances Arabic reading skills among grade XI students. The study underscores the importance of innovative teaching strategies, such as word card media, in facilitating language learning and improving students' academic performance. These insights contribute to the ongoing discourse on pedagogical approaches to enhance reading proficiency in language education.